1. ## Commutative diagram

Hi everyone

I have this diagram, which I must show commutes, i.e. that
$\hat{\beta}\circ (h_{x_0})_*=(h_{x_1})_*\circ \hat{\alpha}$
Where $\alpha$ is a path in X and $\beta=h\circ\alpha$
and $h:X->Y$ is continous with $h(x_0)=y_0$ and $h(x_1)=y_1$

But I'm a little stuck. What I do is this:

Is that correct? But I'm not sure if it's allowed to just say $\overline{h\circ\alpha}=h\circ \bar{\alpha}$. What is the argument for this, that h is continous?

2. Originally Posted by Carl
Hi everyone

I have this diagram, which I must show commutes, i.e. that
$\hat{\beta}\circ (h_{x_0})_*=(h_{x_1})_*\circ \hat{\alpha}$
Where $\alpha$ is a path in X and $\beta=h\circ\alpha$
and $h:X->Y$ is continous with $h(x_0)=y_0$ and $h(x_1)=y_1$

But I'm a little stuck. What I do is this:

Is that correct? But I'm not sure if it's allowed to just say $\overline{h\circ\alpha}=h\circ \bar{\alpha}$. What is the argument for this, that h is continous?
It seems correct to me. Recall that $\alpha$ is a path and $\bar{\alpha}$ is the reverse of $\alpha$. Thus, $\bar{a}(t)=\alpha(1-t)$. Similarly, $\overline{h \circ \alpha}(t) = (h \circ \alpha)(1-t)$. Now we see that $\overline{h \circ \alpha}(t) = h \circ \bar{\alpha}(t)$.